Microplastic Pollution and Corporate Legal Responsibility: Environmental and Business Regulation Perspectives - Hutagalung, Dhaniel (Jurnal Hukum dan Keadilan, 2025)
Microplastic pollution has emerged as a persistent environmental threat due to its microscopic nature, ecological persistence, and ability to enter marine and human food chains. In Indonesia, this problem is intensified by industrial activities that generate microplastic waste without a clear legal framework defining corporate obligations and liability. This study applies a normative juridical approach to examine the adequacy of environmental and business regulations in ensuring legal certainty over corporate responsibility for microplastic pollution. The analysis reveals three structural problems: a legal vacuum regarding the definition and pollution standards of microplastics, ambiguity in determining corporate obligations and liability regimes, and normative conflicts between environmental protection and economic interests. These conditions weaken law enforcement and allow corporations to avoid accountability despite proven ecological risks. The study concludes that effective control of microplastic pollution requires regulatory reform that explicitly recognizes microplastics as a distinct pollution category, harmonizes environmental and business law, and imposes binding preventive and ecological restoration obligations on corporations. Such reform is essential to balance environmental protection with sustainable economic development and to strengthen legal certainty in corporate environmental responsibility.